Luti Gendang Traditional Food Business - Dessy Aliandrina; Ridho Kurnia (ConCEPt - Conference on Community Engagement Project, 2023)
Curry Up is a micro, small and medium enterprise (MSMEs) engaged in culinary tourism. Curry Up is located at the YKB D.16 complex with 8 employees. Curry Up is a family-run business that has been established since 2017. Curry Up sells Luti Gendang and curry puff food, which are typical Riau Islands or Malay food. This traditional food is still rarely known by people in the city of Batam. Therefore, with this business, luti gendang food and also curry puff can be known to all Indonesian people because every region has different food and tastes. Therefore, with social media such as Instagram and Facebook, all people know about luti gendang food. and curry puff is a typical Malay food, especially in Batam and can be souvenirs for traveling and is a culinary tourism destination for residents of Batam City or outside Batam. The data collection carried out in this activity is to collect primary data. The primary data collected was sourced from interviews conducted by the author. Interviews conducted by the author to Curry Up customers. The questions asked in the interview were related to Luti Gendang which is a Core Product from Curry Up.